Nonlinear Impact of Perception of Organizational Politics on Satisfaction with Co-workers and Job Stress - Bhattarai, Ganesh; Pokharel, Dhruba Raj; Budathoki, Prem Bahadur (Rupantaran: A Multidisciplinary Journal, 2020)
Large number of previous studies have tested that perception of organizational politics negatively impact on employee outcomes with linear relationship. To ascertain the condition where perception of organizational politics can be fruitful for employee outcomes, this study measured the nonlinear relationship of perception of organizational politics with satisfaction with co-workers and job stress. 453 employees working with microfinance companies in Kathmandu valley were surveyed to get cross sectional perceptual data. To infer the conclusion, data were analyzed adopting quantitative analysis, deductive reasoning approach as well as positivist research philosophy. Empirical evidences revealed the nonlinear impact of perception of organizational politics on satisfaction with co-workers and job stress. Both high and low levels of perceived organizational politics were harmful for satisfaction with co-workers and job stress. But a medium level of perception of organizational politics was fruitful for satisfaction with co-workers and job stress. The relationship between perception of organizational politics and satisfaction with co-workers was inverted U-shaped and the relationship between perception of organizational politics and job stress was U-shaped. Based on the findings, numbers of practical as well as theoretical implications are suggested.